2020
DOI: 10.1210/jendso/bvaa064
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and Progesterone Levels are Related to Redox Status in the Follicular Fluid During In Vitro Fertilization

Abstract: Studies have reported a possible association between the levels of oxidative stress biomarkers in follicular fluid (FF) and infertility treatment outcomes. FF analysis can provide important information about oocyte quality. This study aimed to evaluate the possible correlation between oxidative stress biomarker and intrafollicular hormone levels and clinical and laboratory parameters in women during controlled ovarian stimulation. These women were undergoing in vitro fertilization with intracytoplasmic sperm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 72 publications
2
10
0
Order By: Relevance
“…The authors have completed their observations on non-human primates with those on human granulosa cells obtained from follicular fluid samples aspirated from patients undergoing an IVF attempt. Consistent with the results in monkeys, human granulosa cells exhibited the age-related downregulation of the transcription of three genes involved in antioxidative pathways-IDH1, PRDX4, and NDUFB10-and this phenomenon was accompanied by an increase in reactive oxygen species and apoptosis in the granulosa cells [18], indicative of oxidative damage as a crucial factor in ovarian functional decay.…”
Section: Cell-signaling Pathwayssupporting
confidence: 82%
See 1 more Smart Citation
“…The authors have completed their observations on non-human primates with those on human granulosa cells obtained from follicular fluid samples aspirated from patients undergoing an IVF attempt. Consistent with the results in monkeys, human granulosa cells exhibited the age-related downregulation of the transcription of three genes involved in antioxidative pathways-IDH1, PRDX4, and NDUFB10-and this phenomenon was accompanied by an increase in reactive oxygen species and apoptosis in the granulosa cells [18], indicative of oxidative damage as a crucial factor in ovarian functional decay.…”
Section: Cell-signaling Pathwayssupporting
confidence: 82%
“…Mitochondrial damage leads to the activation of apoptotic pathways in granulosa cells, which, in turn, decreases the expression of aromatase, which is required for the transformation of androgens to estrogens, thus leading to the prevalence of androgens over estrogens within the follicles [ 18 ]. Androgens and estrogens present in follicular fluid exert rapid non-genomic effects on maturing human oocytes, affecting oocyte cytoplasmic maturation and postfertilization developmental potential rather than the completion of meiosis [ 19 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Support for this assumption comes from several, mainly in vitro, studies. For example, it is demonstrated that granulosa cells isolated from ovine and porcine large antral follicles, are protected from oxidative (H 2 O 2 ) stress-induced apoptosis when the culture medium is supplemented with estradiol [ 13 , 14 ]. Direct in vivo evidence for a physiological role of oxidative stress in antral follicular atresia is still largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…DOR is at the origin of primary ovarian insufficiency (POI) and can be accentuated by a variety of age-unrelated factors [ 7 ], including chromosome X structural abnormalities and X-autosome translocations [ 23 ], single-gene perturbations ( some located on the X-chromosome and others on autosomes [ 24 , 25 ]), mendelian disorders implicated in other pathologies [ 24 ], mutations of genes (both nuclear and mitochondrial ones) affecting mitochondrial function [ 26 , 27 ], and disturbances of cell signaling pathways, especially those involved in cell protection against oxidative stress [ 28 , 29 ]. Independently of the exact cause, DOR and POI converge to mitochondrial damage, oxidative stress, and diminished ATP production, leading to inflammation, apoptosis, and telomere shortening [ 30 ], in addition to a decrease in the production of estradiol by the granulosa cells [ 31 ], a condition known to reduce oocyte developmental potential by causing an imbalance between nongenomic effects of androgens and estrogens at the oocyte surface [ 32 ].…”
Section: Resultsmentioning
confidence: 99%